Examining the Mediating Role of Parental Bonding in the Relationship Between Early Maladaptive Schemas and Marital Quality in Women - Mirzaei, Zahra; Atefeh Hosseininejad, Seyedeh; Hassanshahi, Mohammad Mehdi (Psychology of Woman Journal, 2023)
Objective: The aim of this study was to examine the mediating role of parental bonding in the relationship between early maladaptive schemas and marital quality among women in the city of Shiraz.Methods and Materials: The research method was descriptive-correlational using structural equation modeling. The statistical population of the study included all women in Shiraz in 2023, from which 250 were selected using the convenience sampling method. Data were collected using Young's Early Maladaptive Schema Questionnaire (2005), Fletcher et al.'s Marital Quality Questionnaire (2000), and Parker et al.'s Parental Bonding Instrument (1979). Data were analyzed using structural equation modeling.Findings: The findings of the study indicated that early maladaptive schemas have a significant direct effect on marital quality (P